Transformation of soviet women outlook in the first quarter of XX century in western historiography (Journal of history, 2019)
Relations between man and woman for the whole history of humankind have been in the process of everlasting changes. The role of mandid not change much over times, while the females’ role radically alteredover the last centuries. The society mentality should be taken into account– way of thinking, set of intellectual skills and matrixes, typical for any individual or social group. For us the most exciting is the mental transformation process of a soviet woman. Western researchers see the origin for thatto come out define as first half of the XX century when, in their opinion,was formed «totalitarian system» of the soviet society. оветскогообщества. The article is aimed to understand which factors resulted in women’changes of their centuries formed mental nature. How did the priorities tobe equal to man grow? Whether they covered only family sphere or spreadto career and financial independence? How did the young generation ofwomen get into active political life?